DESIGN OF BEZIER SPLINE SURFACES OVER BIVARIATE NETWORKS OF CURVES - A. P. Pobegailo (Informatika)
The paper presents an approach to construct interpolating spline surfaces over a bivariate net-work of curves with rectangular patches. Patches of the interpolating spline surface are constructed by means of blending their boundaries with special polynomials. In order to ensure a necessary para-metric continuity of the designed surface the polynomials of the corresponding degree must be used. The constructed interpolating spline surfaces have a local shape control. If the surface frame is deter-mined by means of Bezier curves, then patches of the interpolating spline surface are Bezier surfaces. The presented approach to surface modeling can be used in such applications as computer graphics and geometric design.